2022
DOI: 10.3389/fendo.2022.1021704
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal insufficiency in patients with Prader-Willi syndrome

Abstract: The generalized dysfunction of the hypothalamic-pituitary axis in patients with Prader-Willi syndrome (PWS) is the most likely cause of hypogonadism, inadequate growth hormone secretion, excessive appetite and associated obesity, impaired body temperature regulation, and hypothyroidism. The syndrome is also related to an increased risk of central adrenal insufficiency, although its prevalence remains unknown. The results of the studies in which different methods of pharmacological stimulation were used do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In contrast, the H116 phenotype was associated with neuronal activity: synapses, calcium signaling and hippocampal long-term potentiation. We note that several terms enriched for H116 correlate with PWS phenotypes; including hormonal regulation [(GnRH (Miller et al , 2009), parathyroid hormone (Iughetti et al , 2019), aldosterone (Kusz & Gawlik, 2022)], insulin secretion (Lautala et al , 1986), salivary secretion (Hart, 1998), circadian entrainment (Powell et al ., 2013) and addictive behavior (Salles et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the H116 phenotype was associated with neuronal activity: synapses, calcium signaling and hippocampal long-term potentiation. We note that several terms enriched for H116 correlate with PWS phenotypes; including hormonal regulation [(GnRH (Miller et al , 2009), parathyroid hormone (Iughetti et al , 2019), aldosterone (Kusz & Gawlik, 2022)], insulin secretion (Lautala et al , 1986), salivary secretion (Hart, 1998), circadian entrainment (Powell et al ., 2013) and addictive behavior (Salles et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…For example, UPD15 leads to gene imprinting abnormalities in the 15q11q13 region, resulting in Prader-Willi/Angelman syndrome. Prader-Willi syndrome is a rare genetic disorder, characterized by clinical features including hypotonia and weakness, severe obesity, hypogonadism, and intellectual disability [ 6 ]. Patients with Angelman syndrome have clinical manifestations such as intellectual defects, microcephaly, ataxia, and seizures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there is no agreement on the prevalence of CAI during acute stress in PWS ( 12 ). Several studies, in children and adults, using different test methods and definitions of CAI, have shown contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…Underdiagnosing can lead to potentially life-threatening situations such as an adrenal crisis during acute stress, and over diagnosing can lead to overuse of hydrocortisone, which might lead to unnecessary side effects. It is, therefore, important to expand the knowledge about acute stress-related adrenal insufficiency in PWS and to create recommendations on the necessity, frequency and repeating the diagnostic procedures for CAI in PWS ( 12 ). It has been reported that there is a negative correlation between age and the HPA-axis ( 18 , 21 ), which suggest that the response of the HPA-axis during acute stress could change with age.…”
Section: Introductionmentioning
confidence: 99%